Comparison of the inflammatory states of serum and gingival crevicular fluid in periodontitis patients with or without type 2 diabetes mellitus - Xin-Ran Xu; Jing-Ling Xu; Lu He; Xian-E Wang; Hong-Ye Lu; Huan-Xin Meng (Elsevier, 2023)
Background/purpose:There is a two-way relationship between periodontitis and type 2 diabetes mellitus. This study aimed to compare the inflammatory states in serum and gingival crevicular fluid (GCF) in periodontitis patients with or without type 2 diabetes mellitus (T2DM) and healthy subjects. Materials and methods: 20 subjects were systematic and periodontal healthy (H group), 40 subjects were with periodontitis (CP group), and other 40 were with periodontitis and type 2 diabetes mellitus (DC group). Fasting blood glucose (FBG) and HbA1c was tested. GCF and serum level of interleukin (IL) −17, visfatin, receptor activator of nuclear factor-kappa B (NF-κB) ligand (RANKL)/osteoprotegerin (OPG) ratio were measured. Results: The GCF volume, total amount of IL-17, vastatin, RANKL/OPG ratio in GCF and their concentrations in serum were higher (P < 0.05) in CP and DC groups than in H group, which were also higher (P < 0.05) in DC group than in CP group except for visfatin in GCF and IL-17 in serum. At sample sites of PD ≤ 3 mm, GCF volume, IL-17, visfatin and RANKL/OPG ratio in DC and CP groups were higher (P < 0.05) than that in H group, which were also higher in DC group than in CP group either with PD ≤ 3 mm or PD > 3 mm. Inflammatory state in GCF was positively correlated to systemic inflammation, and both of them were positively correlated to FBG. Conclusion: Moderate and severe periodontitis aggravated systemic inflammation. T2DM together with periodontitis resulted in more severe systemic inflammation. The positive correlation between the periodontal and systemic inflammation and their association with FBG indicated an inflammatory link between periodontitis and T2DM.